The Effect of Non-pharmacological Therapy with Soy Milk on the Reduction of Primary Dysmenorrhea Pain in Adolescent Girls - Fitriani, Rani; Setiana, Eva Mesi (Journal of Pharmaceutical and Health Research, 2024)
Dysmenorrhea is a detrimental condition for many women, significantly impacting the health-related quality of life. Non-pharmacological interventions, such as warm compress, balanced nutrition, and adequate rest, play a crucial role as strategies. Particularly, the consumption of high-calcium foods, such as soy, is recognized as an effective solution. This research adopts a Quasi-Experimental design with a Pretest Posttest approach and Control Group Design, involving 10 female students in each group. Statistical analysis employs Paired Sample T-Test and Independent T-test. The research findings reveal a p-value of 0.000, rejecting the null hypothesis (H0), indicating a significant difference in the reduction of dysmenorrhea pain scale after the administration of soy milk and health education intervention (HEI) in adolescent girls at MA Walisongo, North Lampung. The discussion emphasizes the role of calcium in alleviating muscle tension, including the uterine muscles, and the presence of isoflavones in soy that can reduce dysmenorrhea. In conclusion, soy milk has a positive influence on reducing primary dysmenorrhea pain in adolescent girls at MA Walisongo, North Lampung.